Multiphase Modeling of Erosion Wear in Slurry Pipe - Kannojiya, Vikas (My University, 2016)
Erosion wear is a serious problem faced in many industries like chemical industries, gas extraction, mining, power generation. In Indian thermal power plants, approximately 30% of ash is produced as a side product while generating power. This ash possesses highly abrasive characteristics. Pipe line is believed to be economical and eco-friendly way of slurry transport rather than the rail transport or road transport. Due to the presence of abrasives in slurry, a problem of wear is often observed in the pipe lines while conveying it to the ash well for the disposal purpose. Erosion causes the degradation or removal of pipe line material which may results in the failure of pipe. Prevention of piping and tubing from getting eroded is therefore an essential objective. Erosion wear gets influenced by different operating parameters like flow velocity, particle attributes, target property, impact angle etc and thus a complicated phenomenon to understand. Several researches were going on to analyse the influence of different operating parameters on the erosion wear. In this work, computational technique is used to analyse erosion wear of mild steel pipe bend caused by the bottom ash-water slurry. Computational Fluid Dynamics (CFD) code FLUENT 15.0 is applied to investigate the influence of pipe diameter, bending angle, flow velocity and bending radius ratio. Simulation study is carried by considering several pipe bends of different diameters from 50 to 200 mm, bending angles in range of 45 to 900 and bending radius of 1.5 to 2.5 at flow velocity variation from 2 to 8 m/s An Euler-Lagrange model with Standard k-є modelling scheme along with the mixture property was implemented in this work to solve the multiphase flow through the pipe line. The magnitude and location of erosion wear is reported at different operating conditions. The obtained results show good agreement with the previous published findings of several investigators.
ME, MED
Keywords: MULTIPHASE; EROSION WEAR